The Unnaturalness Of Indonesian Public Signs Translation Into English In Medan - S, Selaras (Universitas Muhammadiyah Sumatera Utara, 2021)
This research aimed to discover (1) the kinds of unnatural Indonesian-English translation of public signs in Medan city; (2) To investigate the appropriate techniques to avoid the unnatural Indonesian-English translation of public signs in Medan city. This research was done by applying descriptive qualitative method. The data of this research were Indonesian-English public signs found in Medan city. The data were analyzed by using qualitative descriptive analysis proposed by Miles and Huberman. The findings of this research showed that: (1) there were four kinds of unnatural translation found in Indonesian-English translation of public signs in Medan city. They were spelling mistakes, change or loss information, grammatical mistakes and inappropriate choice of words; (2) There were some techniques can be used to avoid the unnatural translation found in Indonesian-English translation of public signs in Medan city. They were borrowing, adaptation, and transposition technique.